Analiza taksonomiczna ofert pracy pojawiających się w dodatku "Praca" w regionie łódzkim w 2006 roku - Staniec, Iwona; Martin, Marek (Taxonomic Analysis of Job Offers Published in "The Work" the Newspaper Supplement in Lodz Region in 2006, 2008)
In this paper we present the analysis of job offers published in "the Work" the newspaper supplement in Lodz region in 2006. The analysis shows the information about general and specialization demands given by employers towards newly hired staff. The analysis lets identify such requirements as: the knowledge of foreign languages, professional experience, education, driving licence and soft skills.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 7, s. 435-442